Posted by mr jo on November 13, 2002 at 12:17:30:
In Reply to: Re: Damm Derivatives Again!! posted by Jack on November 11, 2002 at 14:50:42:
How about logaritmically!
y'=(x+1)^4(x+2)^2(4/(x+1)+2/(x+2)) Which of course simplifies to the answer below!
: : Hey can anyone tell me how to find the derivative of the function
: : y=(x-1)^4(x+2)^2
: : using differential rules and not by expansion.
: : Thank u....
: : Derek
: :Use y`= f`g+fg`
: :f=(x-1)^4 f`=4(x-1)^3
: :g=(x+2)^2 g`=2(x+2)
: : y`=4(x-1)^3(x+2)^2 + 2(x-1)^4(x+2)
: : The solution makes use of the product rule and the chain rule.
Post a Followup